Low-cost portable throttle curve manipulator for smooth initial movement of an electric vehicle - Dimas Adiputra; Pangestu Widodo; Aldo Juan Widodo; Yosefan Alfeus Bayuaji; Nadia Dinda Pratama Putri (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This research aims to develop a low-cost portable throttle curve manipulator for a smooth initial movement of an electric vehicle. The hardware is mostly made up of an Arduino and a pulse width modulation (PWM)-to- direct current (DC) converter, which can be easily installed in electric vehicle. The manipulator produces a throttle output curve based on the current throttle input. The suitable throttle output curve is investigated in two stages. First, the four throttle curve types are compared based on motor vibration change and total energy usage during initial movement. They are none, linear, exponential, and polynomial curve types with a delay of 1 s. Then, in the second stage, the delay is varied from 0.5 to 2.5 s. The result shows that the linear throttle curve output with a delay of 1 s produces is appropriate to refine the initial movement of an electric vehicle compared to the polynomial and exponential curve types. The brushless DC electric (BLDC) motor vibration change decreases from 148.75 Hz to 107.45 Hz and total energy usage decreases from 90.64 joules to 87.23 joules. Therefore, the research concludes that the low-cost portable throttle curve manipulator can be developed using a linear throttle output curve with a delay of 1 s.